Strategi Bersaing PT. Perusahaan Gas Negara (Persero) Tbk SBU Distribusi Wilayah I - Jomaren Tuah Saragih; Eko Suryadi (Faculty of Economics and Business Udayana University, 2014)
The purpose of thi s research is to analyze competitive strategy implemented by PT Perusahaan Gas Negara(Perser o) Tbk SBU Dist ribusi Wilayah I to face competit ion in downstr eam natural gas industry. Descript ivequalitat ive analysis method is used by carrying out SWOT and V alue Chain Analysis. SWOT analysis is usedto ident ify and evaluate st r ength, weakness, opportunity, and threat of the company, whereas the importantfactors and their r elevance to the futur e ar e ident ified by V alue Chain Analysi s.The r esults show that SBUWilayah I uses best price strategy and gives value added cutomer service by maximizing the use of technologyto create sustainable competitive advantage.